2008
DOI: 10.1017/s1742758408901375
|View full text |Cite
|
Sign up to set email alerts
|

Development and reproductive potential of diamondback moth Plutella xylostella (Lepidoptera: Plutellidae) on cultivated and wild crucifer species in Kenya

Abstract: The development, survival and reproductive potential of diamondback moth Plutella xylostella (Linnaeus) were studied at 25^1 8C in the laboratory in response to two cultivated Brassica oleracea cultivars (cabbage B. oleracea var. capitata and kale B. oleracea var. acephala) and four wild crucifer species Erucastrum arabicum, Raphanus raphanistrum, Rorippa nudiuscula and Rorippa micrantha. Rorippa micrantha was the most preferred species in oviposition choice tests, while cabbage and kale were least preferred. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
2
20
1
Order By: Relevance
“…The results obtained in this study differ from those reported by Kahuthia-Gathu et al (2008) about the preference of P. xylostella for two cultivated and four wild brassicas in laboratory. These authors observed a significant oviposition preference for wild species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results obtained in this study differ from those reported by Kahuthia-Gathu et al (2008) about the preference of P. xylostella for two cultivated and four wild brassicas in laboratory. These authors observed a significant oviposition preference for wild species.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we used excised leaves of the host plants in the preference tests; it is questionable whether this affected the ability of females to discriminate hosts and resulted in the observed lack of preference. Studies with P. xylostella and other lepidopteran species have shown that females are able to discriminate host plants using excised leaves and show a hierarchy of preference similar to the one obtained with the entire plant ( Greenberg et al 2002 , Kahuthia-Gathu et al 2008 ). On the other hand, female preference for some species of wild brassicas may be influenced by emission of volatiles when the host plant is attacked by herbivores or is otherwise injured ( Zhang et al 2008 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although studies on the effects of specific plant chemicals on parasitoid fitness are limited, it is generally concluded that plant defence chemicals mostly have a negative impact on natural enemy traits such as development time, survivorship and body size (Thurston & Fox 1972;Campbell & Duffey 1979, 1981Barbosa et al 1986;El-Heneidy et al 1988;Barbosa et al 1991;Thaler 1999Thaler , 2002Dicke 2006). These effects can strongly vary among plant species (Smith 1957;Altahtawy et al 1976;Bhatt & Singh 1989;Senrayan & Annadurai 1991;Werren et al 1992;Fox et al 1996;Kruse & Raffa 1997;Eben et al 2000;Harvey et al 2003;Zvereva & Rank 2003;Lu et al 2004) and even among cultivars of a same plant species (Kauffman & Flanders 1985;Orr & Boethel 1985;Hare & Luck 1991;Reed et al 1991;Rogers & Sullivan 1991;Riggin et al 1992;Stark et al 1992;Dosdall & Ulmer 2004;Kahuthia-Gathu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(2005) have compared the larval development of P. xylostella on cabbage cultivars and reported that the larvae of P. xylostella develop more rapidly on Green Coronet cabbage than the Savoy King variety. Development period of larvae of P. xylostella is shorter on cabbage than the larvae reared on kale (Kahuthia et al . 2008).…”
Section: Resultsmentioning
confidence: 99%